Tutoring and the Time: An Educational Transactional Analysis Perspective on Tutors' Perception of Time Structuring - Adrianna Regina Sarnat-Ciastko (University of Lower Silesia, 2013)
It would seem that "meeting" is an adequate synonym of term "tutoring". This always has its time and space. Of course, the best situation is when the an unhurried and attentive meeting is based on a mutual attitude of dialogue. In transactional analysis, this form of human relationship is called intimacy. Intimacy is the most valuable type of time structure. and respectively ranks the games, activity, pastimes, ritual and withdrawal. The time structure allows specifing the kind of action plan of the individual and also the nature of its relationships with others. But what do tutors think about these issues? The following article will be an attempt to answer this question. This work will be based on partially directed interviews conducted by the author with an intentionally chosen group of teachers in schools implementing the tutoring method.